Effects of Trehalose and Catalase on the Viability and Kinetic Parameters of Cryopreserved Ram Sperm - Gungor, Sukru; Ata, Ayhan; Inanc, Muhammed Enes (Acta Scientiae Veterinariae, 2018)
Background: Most part of ram spermatozoa membrane has unsaturated fatty acids (phospholipids). Membrane structure of cells is composed of double ordered phospholipid layers adorned with mosaic-like protein, glycoprotein and glycolipids. Sperm freezing protocols could be negatively affected on ram sperm motility, viability and acrosome integrity during cryopreservation. For these reasons, researchers were designed their topics has led to the search for effective antioxidant systems against peroxidative damage and spermatozoon dysfunction. There are three protective enzymatic systems against reactive oxygen species (ROS) damage in sperm. These include superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase / reductase cycles Catalase (CAT) is a hemo-protein in the enzyme tetramer structure. The aim of this study was to investigate the effects of trehalose, catalase and their combinations on ram sperm parameters after the cryopreservation/thawing process. Materials, Methods & Results: At the out of breeding season (March-May) seven rams (1-3 years of age) were used in this study. Ejaculates were collected by electro-ejaculator twice a week. Pooled ejaculates were at 37°C, divided into six aliquots, diluted with the Tris based extender containing Trehalose 25 mM (Group-1), Trehalose 50 mM (Group-2), Catalase 200 µg (Group-3), Catalase 400 µg (Group-4), Trehalose 50 mM + Catalase 400 µg (Group-5) and no anti-oxidant (control), respectively, were cooled to 5°C than frozen in 0.25 mL French straws on the nitrogen vapour and stored in liquid nitrogen. The extender supplemented with Group 1 (54.1 ± 1.53; 73.1 ± 4.37), 50 mM (58.3 ± 4.01; 63.1 ± 0.30) and Group 5 (56.6 ± 1.05; 58.3 ± 0.55) resulted in higher subjective motility in comparison to the control (40.0 ± 3.87; 40.5 ± 0.22) group respectively (P < 0.05). Besides, Group 1 (60.16 ± 4.39) and Group 5 (59.60 ± 2.21) led to higher CASA total motility when compared to control (44.40 ± 8.13) group (P < 0.05). Sperm progressive motility was better in Group 1 (20.57 ± 6.90) than the Group 3 (10.63 ± 3.59) [P < 0.05]. Casa kinetic parameters of catalase 200 (Group 3) was higher values than other groups in VCL, VSL, VAP, LIN parameters (P < 0.05). There were no statistically significant differences on the membrane integrity parameter between the groups (P > 0.05). Discussion: Freezing ram sperm is extremely difficult process when compared bull and dog semen. Previous studies showed that antioxidants which were adding into the ram freezing extender gave positive effects solely or combination. In this study similar results were taken at trehalose 25, 50 mM and trehalose 50 mM + catalase 400 µg except 200 and 400 µg catalase groups. These findings supported some researches but lots of them opposite of catalase results. Catalase is found semen and ameliorates the sperm parameters when adding the liquid storage. Also after diluted and equilibrated catalase groups motilities were better than the control group. During the freezing stage catalase efficiency has been restricted. On the other hand when it combined with the trehalose 50 mM, catalase activity was triggered. Trehalose acts on sperm as non-permanent had a protective action related both osmotic effect and specific interactions with membrane phospholipids. Our data suggest that solely Trehalose 50 mM or combination with Catalase 400 µg can be added to Tris based extender for improving the post-thawed sperm quality in ram semen.